1997
DOI: 10.1038/sj.onc.1201194
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Rho family small GTP-binding proteins with Rho GDP dissociation inhibitor (Rho GDI) in Saccharomyces cerevisiae

Abstract: The small GTP-binding proteins of the Rho family, consisting of the Rho, Rac, and Cdc42 subfamilies, are implicated in various cell functions, such as cell shape change, cell motility and cytokinesis, through reorganization of actin cytoskeleton. Rho GDI is a general regulator which forms a complex with the GDP-bound inactive form of the Rho family members and inhibits their activation. We have purified Rho GDI from the yeast Saccharomyces cerevisiae, cloned its gene, and named it RDII (Rho GD). In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 24 publications
4
51
1
Order By: Relevance
“…RhoGDIa has been described as a ubiquitously expressed protein, which is found primarily in the cytoplasm of cells (Koch et al 1997). Thus, we were surprised when we identified endogenously expressed RhoGDIa from HeLa nuclear extracts as a component of a large multiprotein complex associated with the DNA-bound ERa (Schultz-Norton et al 2007).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…RhoGDIa has been described as a ubiquitously expressed protein, which is found primarily in the cytoplasm of cells (Koch et al 1997). Thus, we were surprised when we identified endogenously expressed RhoGDIa from HeLa nuclear extracts as a component of a large multiprotein complex associated with the DNA-bound ERa (Schultz-Norton et al 2007).…”
Section: Resultsmentioning
confidence: 98%
“…RhoGTPases act as molecular switches cycling between an active, GTP-bound form, which is anchored to the cell membrane, and an inactive, GDP-bound form, which is present in the cytoplasm (Koch et al 1997). When bound to GTP, RhoGTPases interact with downstream effector proteins and foster signal propagation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that Rdi1 is able to extract Cdc42 and Rho1 from membranes (Koch et al, 1997;Eitzen et al, 2001;Richman et al, 2004;Tcheperegine et al, 2005), but it has not been tested whether Rdi1 interacts with other Rho GTPases as well. Therefore, we performed immunoprecipitation experiments with strains in which Rho GTPases were N-terminally tagged with the HA and Rdi1 C-terminally with the myc epitope.…”
Section: Rdi1 Specifically Interacts With Cdc42 Rho1 and Rho4mentioning
confidence: 99%
“…In contrast, others claim that RDI1 overexpression causes only a slightly rounder cell morphology (Tcheperegine et al, 2005). Deletion of RDI1 does not produce any detectable phenotypes in budding yeast (Masuda et al, 1994), but in the human fungal pathogen Candida albicans, cells lacking RDI1 exhibit reduced polarized growth (Court and Sudbery, 2007).Rdi1 is found in the cytoplasm, but it also localizes to the tips of small buds and the bud neck region, where it interacts with Cdc42 (Koch et al, 1997;Richman et al, 2004;Cole et al, 2007). Rdi1 has the ability to extract Cdc42 and Rho1 from vacuolar membranes (Eitzen et al, 2001), and it can also extract Cdc42 from the plasma membrane (Richman et al, 2004;Tcheperegine et al, 2005).…”
mentioning
confidence: 99%